QAShQADARYO VILOYATI MEVA-SABZAVOTChILIK KLASTERLARI RIVOJLANIShINING HUDUDIY XUSUSIYATLARI - Yaxshiboyev, B.A. (SCIENCE and SOCIETY, 2025)
This article analyzes the territorial features of the development of fruit and vegetable clusters in the Kashkadarya region from an economic-geographical point of view. The study took into account the dependence of the clustering process on regional factors, natural-climatic conditions, the potential of irrigated land, the level of employment resources and infrastructure provision. It also shows the territorial differentiation of cluster activities based on the existing fruit and vegetable cultivation base. The article substantiates discrepancies in the possibilities of clustering between the mountainous regions of the Kashkadarya region (Yakkabog, Kitab, Shahrisabz) and the Plains regions (Mirishkor, Nishan, Mubarak). As a result, modern approaches to the organization of fruit and vegetable clusters, mechanisms for strengthening economic efficiency and territorial specialization have been developed in the region.
Keywords: Kashkadarya region; fruit and vegetable; cluster; territorial characteristics; specialization; economic geographical factors; infrastructure; agriculture; resource potential; agroclaster